Effect of current ratio, debt to equity ratio, and return on equity on stock prices (empirical study of textile companies listed on the Indonesian stock exchange) - Eppian Tamba (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2023)
Textile Company is one of the major industries listed on the Indonesia Stock Exchange which has experienced good development from year to year. For this reason, before renting capital by buying shares, an investor can analyze information on the financial performance of other companies, Current Ratio, Debt Equity Ratio and Return On Equity so that potential investors can obtain what is needed. The theory used in this study is a theory related to CR, DER and ROE. The purpose of this study is to prove whether or not the influence of CR, DER and ROE on stock prices in textile companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The total population of all research is 18 companies. The sampling method used is purposive sampling technique. The total sample size is 8 companies. Quantitative data is data used in research. technical data collection using technical documentation by browsing www.idx.co.id. The data analysis technique used EVIEWS 10 in testing panel data regression, F test and t test. The results of this study prove that simultaneously CR, DER and ROE have a significant effect on stock prices. The results of the study partially prove that CR and DER have no and significant effect on the influencing variables, and ROE has a positive and significant effect on stock prices. The coefficient of determination shows a numerical value of 66%, the remaining 34% is explained by other variables that do not have to be studied.